2013
DOI: 10.1088/0264-9381/31/2/025004
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing dimensions and massive gravity

Abstract: Abstract. We show that the ghost-free models of massive gravity and their multigraviton extensions follow from considering higher dimensional General Relativity in Einstein-Cartan form on a discrete extra dimension, according to the Dimensional Deconstruction paradigm. We show that Dimensional Deconstruction is equivalent to a truncation of the Kaluza-Klein tower at the nonlinear level. Higher dimensional gravity is not recovered from a lower dimensional multi-graviton theory in the limit of a continuous extra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 103 publications
1
93
0
Order By: Relevance
“…In [39], however, it has been shown that the non-linear terms (10) and (11) could generate the ghost by using the mini-superspace where…”
Section: Still New Derivative Interaction In Massive Gravity?mentioning
confidence: 99%
See 3 more Smart Citations
“…In [39], however, it has been shown that the non-linear terms (10) and (11) could generate the ghost by using the mini-superspace where…”
Section: Still New Derivative Interaction In Massive Gravity?mentioning
confidence: 99%
“…Then we consider the possibility of other classes of the no-ghost interactions by relaxing the assumption in [39]. In the argument so far, we have considered the terms which have invariance under the general coordinate transformation if the fiducial metric f µν could be a dynamical tensor.…”
Section: Still New Derivative Interaction In Massive Gravity?mentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, the structure of the viable bigravity action is symmetric under exchange of the two metrics. We also note that one could arrive at the double minimal coupling from extra-dimensional constructions [14] attempting to obtain bigravity as the low-energy limit. However, it was very recently shown [15,16] that minimally coupling matter to each metric separately, which is the case we consider here, revives the Boulware-Deser ghost [17].…”
mentioning
confidence: 99%